As condições NNT e NNR na realização de um referencial - Monico, João Francisco Galera [UNESP] (My University, 2005)
In this paper the theoretical fundamentals related to the introduction of NNT (No Net Translation) and NNR (No Net-Rotation) conditions in the realization of a referential are presented. Moreover, aspects related to the implementation are also presented, with special emphasis on the realization from VLBI data, where only scale information is available.
NNT and NNR conditions in the realization of a referential
Keywords: remote sensing